The Effect of Climbing Grammar Mountain Game on Students' Writing Achievement - Azizah, Isnaini; Amalia, Shynta; Iqbal Ramdhani, Muhammad; Mahmudah, Faiqah (International Journal of Education Research and Development, 2022)
The objective of this research is to find out whether or not there is a significant effect of using climbing grammar mountain game on students writing achievement of the eighth-grade students at MTsN 2 Batanghari. This was quantitative research that was conducted with a quasi-experimental design. The subjects in this research were 39 students. The study result showed that the mean of the post-test score (56.62) was higher than the mean of the pre-test score (51.69) in the experimental class. The p-value in the paired sample t-test was less than 0,05 (0,002<0,05). It shows that the result was significantly different. As a result, was accepted. It shows that students' writing ability improved significantly before and after being taught through the climbing grammar mountain game. The p-value for the independent sample t-test in the equal variances assumed and not assumed cases was (0,007<.0,05). It shows that has been accepted and has been rejected. It shows that there was a significant difference between the students who were taught using the climbing grammar mountain game and those who were not.